(untitled) (Journal of Educational Sciences, 2016)
Бұл мақалада гипертекст жəне оның қасиеттері мен типологиясы туралы айтылады, яғни гипертекстің кұрылымын өзге тілдік білім беру моделі ретінде де қарастыруға болады. This article discusses the structure and the different types of the branched texts. The branching scheme can be used as a foreign language education system model, if language levels of Common Framework are divided between the language institutions of the country or different countries.